BUILDING THE HISTORY OF THE FUTURE: A TOOL FOR CULTURE-CENTRED DESIGN FOR THE SPECULATIVE FUTURE. (May 2020) - Dong, F.; Sterling, S.; Schaefer, D.; Forbes, H.
Abstract: In this paper, the authors propose a culture-centred tool called Speculative Ethnography to support the practice of design for the speculative future. Most explorations of tools and techniques of design for the speculative future focus on materialising the speculation. Instead, Speculative Ethnography provides a guideline to help designers define their speculation through the scientific imagination of the plausible future. It ensures the effectiveness of design for the speculative future and supports the interaction of culture and design for the speculative future.